IMPLEMENTING A HYBRID MODEL OF TGFU AND FITNESS EDUCATION TO IMPROVE PHYSICAL FITNESS AND SOCIAL INTELLIGENCE OF ELEMENTARY STUDENTS - Sartika, Jenifer Aprilia; Putri, Wulandari; Nugroho, Wildan Alfia; Mahendra, Agus; Lubay, Lukmannul Haqim (Ilmu Olahraga, 2025)
This study aims to improve students’ physical fitness and social intelligence through the implementation of a hybrid model combining Teaching Games for Understanding (TGFU) and Fitness Education. The research employed a Classroom Action Research (CAR) design conducted in two cycles. The subjects were 28 fifth-grade students at SDPN 252 Setiabudi. Each cycle consisted of three stages: two learning interventions and one evaluation. Instruments used in the study included the Indonesian Students' Physical Fitness Test (TKSI) and the Social Intelligence Scale (TSIS). The results showed that the hybrid TGFU and Fitness Education model progressively improved students’ physical fitness levels from lower to higher categories. In the pre-cycle stage, low categories such as "very poor" and "poor" comprised 40% of students, 46% were in the "moderate" category, 14% in the "good" category, and none in the "excellent" category. After the second cycle, only 4% of students remained in the low categories, 11% were in the "moderate" category, while the "good" and "excellent" categories increased to 46% and 43%, respectively. In terms of social intelligence, students initially already demonstrated relatively high levels. In the pre-cycle, no students were categorized as "very poor" or "poor", 25% were in the "fair" category, 75% in the "good" category, and none in the "excellent" category. By the end of the second cycle, the percentage of students in the "good" category rose to 79%, "excellent" to 14%, and "fair" decreased to only 7%. In conclusion, the hybrid model of TGFU and Fitness Education proved effective in enhancing both the physical fitness and social intelligence of elementary school students.